Work Stressors and Occupational Health of Young Employees: The Moderating Role of Work Adaptability - Zhou, Houyu; Zheng, Quangquang (Frontiers in Psychology, 2022)
Work adaptability refers to the work experience, habits, and skills that enable an individual to adapt to current or changing work tasks and situations. It is a coping resource that individuals use to mitigate various types of stress. Adopting the interaction model of work stress, this study investigated 168 young employees in 20 organizations in Zhejiang Province through interview research and a questionnaire survey. The results show that work adaptability has a significant main effect on occupational health. The work adaptability of employees plays a moderating role in the relationship between occupational health and lack of work meaning stress, role conflict stress, interpersonal relationship stress, negative organizational atmosphere stress, and total score of work stressors. Young employees with high work adaptability have worse occupational health under high-level stress situations due to a lack of work meaning. For promoting occupational health in young employees, organizations should have this group of workers complete meaningful jobs or inform them of the importance of their jobs, reduce role conflict, and create a supportive organizational atmosphere. For management, it is imperative to eliminate high-level stress that stems from a lack of work meaning in order to retain young employees with high work adaptability. These findings shed light on how work adaptability helps young employees deal with stress and improve their occupational health. In organizational and self-stress management, it is beneficial to improve employees’ work adaptability continuously as a means of effectively resisting stress and maintaining occupational health.